Enhanced detection of emotional facial expressions in Borderline personality disorder - Schulze, Lars; Domes, Gregor; Köppen, Dürken; Herpertz, Sabine (Psychopathology, 2013)
Background: Borderline personality disorder (BPD) is commonly proposed to be characterized by an enhanced sensitivity for emotional stimuli. In the present study, we investigated whether BPD patients show a superior detection of emotional facial expressions relative to healthy controls. The detection of emotional information in the environment represents an important facet of emotional sensitivity. Sampling and Methods: Twenty patients with BPD were compared with 25 healthy controls. The participants were presented a rapid, continuous stream of neutral and randomly inserted emotional facial expressions and were asked to report the presentation of an emotional facial stimulus after each trial. Availability of cognitive resources was manipulated via two different task demands. Results: The participants with BPD performed significantly better in the detection of positive and negative facial expressions compared to the healthy controls. False alarm rates did not differ significantly between the two groups. Conclusions: The BPD participants showed an enhanced detection of emotional expressions that might be related to the emotional disturbances they experience. In particular, we will discuss the role of this superior emotion detection (in combination with previously reported deficits in the labeling of emotional states) for the understanding of emotional instability in BPD.